ABDULKARIM SOTUK BUGROKHAN AND HIS PLACE IN THE POLITICAL HISTORY OF THE KARAKHANID STATE (Eureka Journal of Humanities and Social Research, 2026)
The article is dedicated to highlighting the personality and activities of Abdukarim Sotuq Bugrokhan, who played an important role in the initial stage of development of the Karakhanid state. The acceptance of Islam by Sotuq Bugrokhan in the historical context, the impact of this decision on the state administration and political structure are analyzed. Also, during his reign, the formation of religious ideology, the integration of Turkish traditions and Islamic values, and the processes of political stabilization of the Karakhanid state are highlighted. Also, the activity of Sotuk Bugrokhan is evaluated as one of the important factors in the formation of Islamic state traditions in Central Asia.
Keywords: Movarounnahr, Karakhanids, Talas, Qibray, Abdulkarim Sotuk Bugrokhan, Islam religion, Holy Qur'an, Muslim culture, Mosque, Caravan.